The future is ours: Terminal year end report: AMF Metal Industries Corporation - Chan, Jerez S. (Animo Repository, 2021)
From nothing to a milestone, AMF Metal Industries Corporation is living proof that possibilities are endless. In our journey with AMF Metal Industries Corporation, we were introduced to various strategies that continuously aid the company to keep thriving for growth and sustainability. Although like any other company, the business also had its ups and downs especially during the time of the pandemic. AMF Metal Industries Corporation was one of the many businesses that struggled for months, unable to operate due to the implementation of strict community quarantine procedures. Our timing became relevant. Aside from the fact that the company was in state on uncertainty, AMF was greatly challenged by the circumstances. With this, as soon as we became part of the company, our first focus was on determining how to keep the business alive despite the existence of limitations caused by the pandemic. We were able to transform the problem into opportunities through the activities we planned on.